Negative electrode composition, negative electrode for lithium secondary battery comprising same, and lithium secondary battery comprising negative electrode
By adding specific metal composites to the negative electrode composition of the lithium secondary battery, the problem of volume expansion of the silicon-based active material causing disconnection of the conductive path during charging and discharging is solved, and the service life and capacity density of the battery are significantly improved.
Patent Information
- Application Number
- CN202380054467.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-12-23
- Filing Date
- 2023-12-22
- Publication Date
- 2025-02-21
AI Technical Summary
When using silicon-based active material as the negative electrode active material, volume expansion during charging and discharging leads to disconnection of the conductive path, deteriorating the battery characteristics, and the prior art measures have limitations, making it difficult to effectively solve this problem.
A specific highly reactive metal composite is included in the negative electrode composition. The weight ratio of metal to lithium oxide in the metal composite is 10:1 or more and 800:1 or less, and the content in 100 parts by weight of the negative electrode composition is 1 part by weight or more and 15 parts by weight or less.
By limiting the volume expansion of the silicon-based active material, inhibiting the disconnection of the conduction path, the service life performance of the lithium secondary battery is significantly improved, and the capacity density and cycle stability of the battery are improved.
Smart Images

Figure CN119497916A_ABST
Abstract
Description
Technical Field
[0001] This application claims the benefit of priority of Korean Patent Application No. 10-2022-0183765 filed in the Korean Intellectual Property Office on December 16, 2022, the entire contents of which are incorporated herein by reference.
[0002] The present application relates to a negative electrode composition, a negative electrode for a lithium secondary battery comprising the negative electrode composition, and a lithium secondary battery comprising the negative electrode. Background Art
[0003] Because the use of fossil fuels has increased rapidly, the demand for the use of alternative or clean energy has been increasing, and as part of this trend, the most active field of research is the field of power generation and storage using electrochemical reactions.
[0004] Currently, representative examples of electrochemical devices using such electrochemical energy include secondary batteries, and their use fields are increasing.
[0005] With the technological development and increase in demand of mobile devices, the demand for secondary batteries as energy sources has increased rapidly. Among these secondary batteries, lithium secondary batteries with high energy density and voltage, long cycle life and low self-discharge rate have been commercialized and widely used. In addition, as an electrode for such a high-capacity lithium secondary battery, a method for preparing a high-density electrode with higher energy density per unit volume has been actively studied.
[0006] Generally, a secondary battery is composed of a positive electrode, a negative electrode, an electrolyte, and a separator. The negative electrode contains a negative electrode active material for inserting and extracting lithium ions from the positive electrode, and as the negative electrode active material, silicon-based particles having a high discharge capacity can be used.
[0007] In particular, recently, in order to respond to the demand for high-density energy batteries, there has been an active effort to simultaneously use silicon-based compounds such as Si / C or SiO x Silicon compounds such as Si / C or SiO have been studied as methods for increasing the capacity of negative electrode active materials. x The capacity is 10 times higher than that of graphite-based materials. Silicon-based compounds, which are high-capacity materials, have a larger capacity than the currently used graphite, but there is a problem that the volume expands rapidly during charging and disconnects the conductive path, thereby deteriorating the battery characteristics.
[0008] Therefore, in order to solve the problems when silicon-based compounds are used as negative electrode active materials, measures for adjusting the driving potential, additional measures for suppressing the volume expansion thereof such as further coating the active material layer with a thin film and adjusting the particle size of the silicon-based compound, various measures for preventing the disconnection of the conductive path, etc. have been discussed, but the application of the measures is limited because the performance of the battery may be deteriorated, so that there are still limitations in the commercialization of batteries with negative electrodes having a high content of silicon-based compounds.
[0009] That is, the negative electrode using silicon-based active materials needs to ensure the stability of service life, and the volume of the silicon-based active material changes due to the insertion and deintercalation of lithium during the reaction between lithium and silicon during the charge and discharge process, and the degree of cracking of the active material also becomes serious during the insertion and deintercalation reaction of a large amount of lithium.
[0010] Related research such as limiting the SOC of the silicon-based active material is required in order to ensure the service life characteristics by improving the cracking phenomenon of the silicon-based active material as described above.
[0011] Related technical literature
[0012] (Patent Document 1) Japanese Patent Application Publication No. 2009-080971 Summary of the invention
[0013] [Technical issues]
[0014] It has been found that when, instead of adjusting the SOC of the silicon-based negative electrode system itself, a highly reactive metal complex "that reacts with lithium at a higher potential than silicon during battery discharge" is included in the negative electrode composition, the service life performance can be effectively improved because the SOC of the silicon-based active material itself is limited.
[0015] Therefore, the present application relates to a negative electrode composition, a negative electrode for a lithium secondary battery comprising the negative electrode composition, and a lithium secondary battery comprising the negative electrode.
[0016] [Technical solution]
[0017] An exemplary embodiment of the present specification provides a negative electrode composition, the negative electrode composition including:
[0018] Silicon-based active materials;
[0019] A negative electrode conductive material; and
[0020] Negative electrode binder,
[0021] wherein the negative electrode composition comprises a metal composite having lithium oxide deposited thereon,
[0022] The weight ratio of the metal to the lithium oxide in the metal composite satisfies 10:1 or more and 800:1 or less, and
[0023] The content of the metal composite is 1 part by weight or more and 15 parts by weight or less based on 100 parts by weight of the negative electrode composition.
[0024] Another exemplary embodiment provides a negative electrode for a lithium secondary battery, the negative electrode comprising:
[0025] a negative electrode current collector layer; and
[0026] A negative electrode active material layer is provided on one surface or both surfaces of the negative electrode current collector layer,
[0027] The negative electrode active material layer comprises the negative electrode composition according to the present application or a cured product thereof.
[0028] Finally, a lithium secondary battery is provided, which includes: a positive electrode; a negative electrode for a lithium secondary battery according to the present application; a separator disposed between the positive electrode and the negative electrode; and an electrolyte.
[0029] Beneficial Effects
[0030] A negative electrode composition according to an exemplary embodiment of the present invention is characterized in that, when a high-capacity battery is manufactured using a silicon-based active material as a high-capacity material, a problem caused by volume expansion of the silicon-based active material is improved by including a specific metal composite in the negative electrode composition, not by limiting the SOC in the battery system.
[0031] Particularly, the metal composite is characterized in that a weight ratio of metal to lithium oxide in the metal composite satisfies 10:1 or more and 800:1 or less, and a content of the metal composite is 1 part by weight or more and 15 parts by weight or less based on 100 parts by weight of the negative electrode composition.
[0032] Since the SOC of silicon itself is limited by using the metal composite as described above, the life performance is improved compared to using the silicon-based active material alone. That is, the metal composite has the above-mentioned characteristics, so that it reacts with lithium at a higher potential than the silicon-based active material and has excellent reactivity, thereby suppressing the volume expansion of the silicon-based active material during charge and discharge compared to when the silicon-based active material is used alone, so that the metal composite has the characteristics of excellent effect of improving the life performance.
[0033] Furthermore, when a metal composite having lithium oxide deposited thereon is included as in the present invention, lithium ions are evenly distributed at the upper and lower ends of the electrode during the initial electrochemical reaction, compared to a case where only metal oxide is used, thereby being able to achieve an effect of improving the tortuosity of the electrode by enabling lithium ions to be added more evenly.
[0034] That is, the main purpose of the present invention is that the negative electrode composition according to the present application can obtain a negative electrode with high capacity and high density by having a high content of silicon-based active material particles. At the same time, in order to solve problems such as volume expansion caused by the high content of silicon-based active material particles, a metal composite with a specific composition and content is used. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 It is a view showing a stack structure of a negative electrode for a lithium secondary battery according to an exemplary embodiment of the present application.
[0036] Figure 2 It is a view showing a stack structure of a negative electrode for a lithium secondary battery according to an exemplary embodiment of the present application.
[0037] Figure 3 is a view showing a stack structure of a lithium secondary battery according to an exemplary embodiment of the present application.
[0038] <Reference Numbers>
[0039] 10: Negative electrode collector layer
[0040] 20: Negative electrode active material layer
[0041] 30: Diaphragm
[0042] 40: Positive electrode active material layer
[0043] 50: Positive electrode collector layer
[0044] 100: Negative electrode for lithium secondary battery
[0045] 200: Positive electrode for lithium secondary battery DETAILED DESCRIPTION
[0046] Before describing the present invention, some terms are first defined.
[0047] In the present specification, when a part “comprises” a constituent element, unless otherwise specifically stated, this does not mean that another constituent element is excluded but means that another constituent element may further be included.
[0048] In this specification, "p to q" means a range of "p or more and q or less".
[0049] In this specification, the "specific surface area" is measured by the BET method, specifically, calculated from the nitrogen adsorption at liquid nitrogen temperature (77 K) using BELSORP-mini II manufactured by BEL Japan, Inc. That is, in this application, the BET specific surface area may refer to the specific surface area measured by the measurement method.
[0050] In this manual, "D n " refers to the particle size distribution, and refers to the particle size at the n% point of the cumulative distribution of the number of particles according to the particle size. That is, D 50 D is the particle size at the 50% point of the cumulative distribution of particle numbers according to particle size (average particle size), 90 is the particle size at the 90% point of the cumulative distribution of particle numbers according to particle size, and D 10 It is the particle size at the 10% point of the cumulative distribution of the number of particles according to the particle size. On the other hand, the particle size distribution can be measured using a laser diffraction method. Specifically, after the powder to be tested is dispersed in a dispersion medium, the particle size distribution is calculated by introducing the resulting dispersion into a commercially available laser diffraction particle size measuring device (e.g., Microtrac S3500) to measure the difference in the diffraction pattern as the particle size changes when the particle passes through the laser beam.
[0051] In the present specification, the fact that a polymer contains a monomer as a monomer unit means that the monomer participates in a polymerization reaction and is therefore contained in the polymer as a repeating unit. In the present specification, when a polymer contains a monomer, it is interpreted as the same as when the polymer contains a monomer as a monomer unit.
[0052] In this specification, "polymer" is understood to be used in a broad sense, including copolymers, unless otherwise specified as a "homopolymer".
[0053] In this specification, the weight average molecular weight (M w ) and number average molecular weight (M n ) is a polystyrene-converted molecular weight measured by gel permeation chromatography (GPC) using commercially available monodisperse polystyrene polymers (standard samples) with various polymerization degrees for measuring molecular weight as standard materials. In this specification, unless otherwise specified, molecular weight refers to weight average molecular weight.
[0054] Hereinafter, the present invention will be described in detail with reference to the accompanying drawings so that those skilled in the art can easily implement the present invention. However, the present invention can be implemented in various forms and is not limited to the following description.
[0055] An exemplary embodiment of the present specification provides a negative electrode composition, the negative electrode composition comprising: a silicon-based active material; a negative electrode conductive material; and a negative electrode binder, wherein the negative electrode composition comprises a metal complex on which a lithium oxide is deposited, and the weight ratio of the metal to the lithium oxide in the metal complex satisfies 10:1 or more and 800:1 or less, and based on 100 parts by weight of the negative electrode composition, the content of the metal complex is 1 part by weight or more and 15 parts by weight or less.
[0056] Since using the metal complex as described above limits the SOC of silicon itself compared to using only the silicon-based active material, it has the effect of improving the service life performance. That is, the metal complex has the above characteristics, whereby it reacts with lithium at a higher potential than the silicon-based active material and has excellent reactivity. Therefore, compared to using only the silicon-based active material, the volume expansion of the silicon-based active material during charge and discharge can be suppressed, and thus the metal complex has excellent characteristics of improving the service life performance.
[0057] An exemplary embodiment of the present application includes the negative electrode composition, wherein the silicon-based active material includes one or more selected from SiO x (x = 0), SiO x (0 < x < 2), SiC, and Si alloys.
[0058] The active material of the present invention includes a silicon-based active material. The silicon-based active material may be SiO x , Si / C, and Si. SiO x may include a compound represented by SiO x (0 ≤ x < 2). Since SiO2 does not react with lithium ions and thus cannot store lithium, it is preferred that x is within the above range. The silicon-based active material may be Si / C composed of a composite of Si and C; or Si. In addition, two or more of the above silicon-based active materials may be used in a mixture form. The negative electrode active material may further include a carbon-based active material on the basis of containing the above silicon-based active material. The carbon-based active material may contribute to improving the excellent cycle characteristics or battery service life performance of the negative electrode or secondary battery of the present invention.
[0059] Generally, it is known that the capacity of the silicon-based active material is more than 10 times higher than that of the carbon-based active material. Therefore, when the silicon-based active material is applied to the negative electrode, it is expected that an electrode with a high energy density even with a small thickness can be achieved.
[0060] An exemplary embodiment of the present application provides a negative electrode composition, wherein the silicon-based active material includes one or more selected from SiO x (x = 0) and SiO xOne or more of (0 < x < 2), and based on 100 parts by weight of the silicon-based active material, the SiO x (where x = 0) has a content of 70 parts by weight or more.
[0061] In another exemplary embodiment, based on 100 parts by weight of the silicon-based active material, the silicon-based active material may contain 70 parts by weight or more, preferably 80 parts by weight or more, more preferably 90 parts by weight or more and 100 parts by weight or less, preferably 99 parts by weight or less, more preferably 95 parts by weight or less of SiO x (where x = 0).
[0062] Based on 100 parts by weight of the silicon-based active material, the silicon-based active material according to the present application may contain 70 parts by weight or more of SiO x (where x = 0), while the disadvantage of using a silicon-based active material with a SiO x (0 < x < 2) - based material as the main material is that its theoretical capacity is far less than that of the silicon-based active material of the present application. That is, when using a SiO x (0 < x < 2) - based active material, no matter what kind of treatment is carried out on the active material itself, compared with the case of having the silicon-based active material of the present invention, conditions equivalent to the charge-discharge capacity cannot be achieved.
[0063] In an exemplary embodiment of the present application, for the silicon-based active material, pure silicon (Si) may be used as the silicon-based active material. Using pure silicon (Si) as the silicon-based active material may mean that, based on the total 100 parts by weight of the silicon-based active material as described above, the content of pure silicon particles (SiO x (where x = 0)) not combined with other particles or elements is within the above range.
[0064] Because the silicon-based active material has a significantly higher capacity than the graphite-based active material used in the related art, attempts to apply the silicon-based active material have been increasing. However, the attempts are limited to cases such as mixing a small amount of the silicon-based active material with the graphite-based active material and using them, because the silicon-based active material has a high volume expansion rate during the charge-discharge process.
[0065] Therefore, the present invention is characterized in that while using a high content of the silicon-based active material as the negative electrode active material to improve the capacity performance, a metal complex under specific conditions is used to solve the problems of maintaining the conduction path due to volume expansion as described above, and maintaining the binding between the conductive material, the binder, and the active material.
[0066] On the other hand, the average particle size (D 50) may be 5 μm to 10 μm, specifically 5.5 μm to 8 μm, and more specifically 6 μm to 7 μm. When the average particle size is included in the above range, because the specific surface area of the particles is included in a suitable range, the viscosity of the negative electrode slurry is formed in a suitable range. Therefore, it is beneficial to disperse the particles constituting the negative electrode slurry. In addition, the size of the silicon-based active material has a value equal to or greater than the lower limit value range, and because the composite composed of the conductive material and the binder in the negative electrode slurry makes the contact area between the silicon particles and the conductive material excellent, the possibility of the conductive network continuing increases, thereby improving the capacity retention rate. On the other hand, when the average particle size satisfies the above range, excessively large silicon particles are eliminated, thereby forming a smooth negative electrode surface, thereby preventing the phenomenon of uneven current density during charge and discharge.
[0067] In an exemplary embodiment of the present application, the silicon-based active material generally has a characteristic BET specific surface area. The BET specific surface area of the silicon-based active material is preferably 0.01 m 2 / g to 150.0 m 2 / g, more preferably 0.1m 2 / g to 100.0 m 2 / g, particularly preferably 0.2 m 2 / g to 80.0 m 2 / g, and most preferably 0.2 m 2 / g to 18.0 m 2 The BET specific surface area is measured according to DIN 66131 (using nitrogen).
[0068] In an exemplary embodiment of the present application, the silicon-based active material may be present, for example, in a crystalline or amorphous form, and is preferably not porous. The silicon particles are preferably spherical or fragmentary particles. Alternatively, but less preferably, the silicon particles may also have a fibrous structure or be present in the form of a film or coating containing silicon.
[0069] In an exemplary embodiment of the present application, a negative electrode composition is provided, wherein the content of the silicon-based active material is 60 parts by weight or more based on 100 parts by weight of the negative electrode composition.
[0070] In another exemplary embodiment, the content of the silicon-based active material may be 60 parts by weight or more, preferably 65 parts by weight or more, more preferably 70 parts by weight or more, and may be 95 parts by weight or less, preferably 90 parts by weight or less, more preferably 85 parts by weight or less, based on 100 parts by weight of the negative electrode composition.
[0071] The negative electrode composition according to the present application is characterized in that even if a silicon-based active material having a very high capacity is used within the above range, by using a specific metal composite capable of suppressing the volume expansion rate during charge and discharge, the performance of the negative electrode does not deteriorate even when the content is within the above range and the output characteristics during charge and discharge are also excellent.
[0072] In an exemplary embodiment of the present application, the silicon-based active material may have a non-spherical shape, and the sphericity thereof is, for example, 0.9 or less, for example, 0.7 to 0.9, for example, 0.8 to 0.9, for example, 0.85 to 0.9.
[0073] In the present application, sphericity is determined by the following formula 1-1, where A is the area and P is the boundary line perimeter.
[0074] [Formula 1-1]
[0075] 4πA / P 2
[0076] In an exemplary embodiment of the present application, the negative electrode composition may include a metal composite on which lithium oxide is deposited.
[0077] The metal composite on which lithium oxide is deposited is different from the existing concept of using metal oxides. That is, metal oxide can be represented by MO2 (M is a metal), and the metal composite on which lithium oxide is deposited in the present application can have a structure in which lithium oxide is deposited on the metal itself. When metal oxide (or metal) is used in the negative electrode, lithium ions need to enter from the top to the bottom of the electrode during the first discharge, resulting in a relative imbalance between the upper and lower parts of the electrode, and thus the service life performance is degraded. However, according to the metal composite on which lithium oxide is deposited in the present application, lithium oxide can be uniformly mixed, so that when the initial electrochemical reaction occurs, lithium ions are distributed as a whole at the upper and lower ends of the electrode, so that the introduction of lithium ions is more uniform, so that the effect of improving curvature can be exerted.
[0078] In an exemplary embodiment of the present application, a weight ratio of the metal to the lithium oxide in the metal composite may satisfy 10:1 or more and 800:1 or less.
[0079] In another exemplary embodiment, the weight ratio of the metal to the lithium oxide in the metal composite may be 10:1 or more and 800:1 or less, preferably 15:1 or more and 700:1 or less, and more preferably 20:1 or more and 600:1 or less.
[0080] The metal composite according to the present application is equivalent to a material for limiting the SOC of the silicon-based active material. In the case of the metal composite according to the present application, lithium oxide can be deposited on the surface of the metal. In particular, the metal composite according to the present application satisfies the ratio of lithium oxide to metal in the above ratio, and reacts with lithium at a higher potential than the silicon-based active material, and has excellent reactivity, so compared with the case where the silicon-based active material is used alone, the volume expansion of the silicon-based active material during the charge and discharge process can be suppressed, so the metal composite has excellent characteristics of improving the service life performance.
[0081] That is, when the ratio of lithium oxide in the metal composite is low, there may be a problem that the metal composite cannot react uniformly with Li in the metal during the reaction process, and when the ratio of lithium oxide exceeds the above range, even if these materials react, these materials may remain, causing the resistance to increase, thereby causing the battery performance to deteriorate.
[0082] An exemplary embodiment of the present application provides a negative electrode composition, wherein the content of the metal composite is 1 part by weight or more and 15 parts by weight or less based on 100 parts by weight of the negative electrode composition.
[0083] In another exemplary embodiment, the content of the metal composite may be 1 part by weight or more and 15 parts by weight or less, preferably 2 parts by weight or more and 14 parts by weight or less, and more preferably 3 parts by weight or more and 13.5 parts by weight or less, based on 100 parts by weight of the negative electrode composition.
[0084] An exemplary embodiment of the present application provides a negative electrode composition, wherein a weight ratio of the metal composite: the silicon-based active material in the negative electrode composition satisfies 1:5 to 1:20.
[0085] The negative electrode composition according to the present application is characterized in that a silicon-based active material is used and the above-mentioned metal composite is included at the same time, and the above-mentioned weight ratio is satisfied. When the above-mentioned weight ratio is included, the content of the silicon-based active material itself is not reduced, so that high energy density and high capacity can be exhibited, while the metal composite is included in an appropriate content to limit SOC, thereby having a feature that the service life characteristics can also be improved.
[0086] That is, when the content of the metal composite is lower than the above range, the degree of limiting the SOC of Si becomes smaller, so the cracking phenomenon of Si cannot be alleviated, and when the content of the metal composite exceeds the above range, the discharge capacity of the metal relative to Si is reduced, so the total load in the negative electrode may increase, resulting in an increase in electrode resistance.
[0087] In an exemplary embodiment of the present application, the metal may be Sn.
[0088] In an exemplary embodiment of the present application, as the lithium oxide, any lithium oxide may be used without any limitation as long as it is a lithium oxide used in the art, and Li 2 O may be used.
[0089] In an exemplary embodiment of the present application, the content of the lithium oxide may be 5 parts by weight or less, preferably 3 parts by weight or less, and more preferably 1 part by weight or less, based on 100 parts by weight of the negative electrode composition.
[0090] An exemplary embodiment of the present application provides a negative electrode composition, wherein the lithium oxide has a D of 200 nm or less. 50 Particle size.
[0091] In another exemplary embodiment, the lithium oxide has a D 50 The particle size may be 200 nm or less, preferably 150 nm or less, and specifically may be within the range of 10 nm or more and 30 nm or less.
[0092] Lithium oxide is deposited on the metal surface. When the particle size is within the above range, the deposition ability on the metal surface can be improved, and the lithium oxide also has the characteristic of having an appropriate degree of dispersion.
[0093] In the prior art, only graphite compounds are generally used as negative electrode active materials, but in recent years, as the demand for high-capacity batteries increases, attempts to mix and use silicon compounds to increase capacity have increased. However, in the case of silicon compounds, even if the properties of the silicon active material itself are adjusted as described above according to the present application, the volume expands rapidly during the charge and discharge process, so in some cases, the problem of damage to the conductive path formed in the negative electrode active material layer may occur.
[0094] Therefore, in an exemplary embodiment of the present application, the negative electrode conductive material may include one or more selected from a point-shaped conductive material, a surface-shaped conductive material, and a line-shaped conductive material.
[0095] In an exemplary embodiment of the present application, the dot-shaped conductive material can be used to enhance the conductivity of the negative electrode, and refers to a conductive material in a dot-shaped or spherical shape that has conductivity without causing chemical changes. Specifically, the dot-shaped conductive material can be at least one selected from the following: natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, conductive fiber, fluorocarbon, aluminum powder, nickel powder, zinc oxide, potassium titanate, titanium oxide, and polyphenylene derivatives, and in terms of achieving high conductivity and excellent dispersibility, carbon black may be preferably included.
[0096] In an exemplary embodiment of the present application, the dot-shaped conductive material may have a diameter of 40 m 2 / g and above 70 m 2 / g or less, preferably 45 m 2 / g and above 65 m 2 / g or less, more preferably 50 m 2 / g and above 60 m 2 / g or less BET specific surface area.
[0097] In an exemplary embodiment of the present application, the functional group content (volatile matter) of the dot-shaped conductive material may satisfy 0.01% to 1%, preferably 0.01% to 0.3%, and more preferably 0.01% to 0.1%.
[0098] In particular, when the functional group content of the dot-shaped conductive material satisfies the above range, functional groups exist on the surface of the dot-shaped conductive material, so that when water is used as a solvent, the dot-shaped conductive material can be smoothly dispersed in the solvent. In particular, in the present invention, because silicon particles and a specific binder are used, the functional group content of the dot-shaped conductive material can be reduced, so the present invention has an excellent effect of improving dispersibility.
[0099] In an exemplary embodiment of the present application, it is characterized in that, in addition to containing the silicon-based active material, a dot-shaped conductive material having a functional group content within the above range is further contained, and the functional group content can be adjusted according to the degree of heat treatment of the dot-shaped conductive material.
[0100] In an exemplary embodiment of the present application, the particle size of the dot-shaped conductive material may be 10 nm to 100 nm, preferably 20 nm to 90 nm, and more preferably 20 nm to 60 nm.
[0101] In an exemplary embodiment of the present application, the negative electrode conductive material may include a planar conductive material.
[0102] The planar conductive material can be used to improve conductivity by increasing surface contact between silicon particles in the negative electrode while suppressing disconnection of the conductive path due to volume expansion. The planar conductive material can be in the form of a plate-like conductive material or a block-like conductive material.
[0103] In an exemplary embodiment of the present application, the planar conductive material may be provided in a form of being bonded to the surface of the silicon-based particles. Specifically, the planar conductive material may be provided in a form of -OH groups or -O groups on the surface of the silicon-based particles bonding to the hydrophilic groups of the planar conductive material.
[0104] In an exemplary embodiment of the present application, the planar conductive material may include at least one selected from plate-like graphite, graphene, graphene oxide, and graphite flakes, and may preferably be plate-like graphite.
[0105] In an exemplary embodiment of the present application, the planar conductive material may have an average particle size (D 50 ). When the average particle size satisfies the above range, sufficient particle size promotes dispersion without causing excessive increase in viscosity of the negative electrode slurry. Therefore, when the same equipment and time are used to disperse the particles, the dispersion effect is excellent.
[0106] In an exemplary embodiment of the present application, a negative electrode composition is provided, wherein the D of the planar conductive material is 10 0.5 μm or more and 2.0 μm or less, D 50 is 2.5 μm or more and 3.5 μm or less, and D 90 It is 6.5 μm or more and 15.0 μm or less.
[0107] In an exemplary embodiment of the present application, as the planar conductive material, a planar conductive material with a high specific surface area having a high BET specific surface area or a planar conductive material with a low specific surface area may be used.
[0108] In an exemplary embodiment of the present application, as the planar conductive material, a planar conductive material with a high specific surface area or a planar conductive material with a low specific surface area can be used without limitation, but specifically, the planar conductive material according to the present application may affect the electrode performance to a certain extent due to the dispersion effect, and therefore it may be particularly desirable to use a planar conductive material with a low specific surface area that does not cause dispersion problems.
[0109] In an exemplary embodiment of the present application, the planar conductive material may have a size of 1 m 2 / g or more BET specific surface area.
[0110] In another exemplary embodiment, the planar conductive material may have a size of 1 m 2 / g and above 500 m 2 / g or less, preferably 5 m 2 / g and above 300 m 2 / g or less, more preferably 5 m 2 / g and above 250 m 2 / g or less BET specific surface area.
[0111] As the planar conductive material according to the present application, a planar conductive material having a high specific surface area or a planar conductive material having a low specific surface area can be used.
[0112] In another exemplary embodiment, the planar conductive material is a planar conductive material with a high specific surface area, and the BET specific surface area may satisfy 50 m 2 / g and above 500 m 2 / g or less, preferably 80 m 2 / g and above 300 m 2 / g or less, more preferably 100 m 2 / g and above 300 m 2 / g or less.
[0113] In yet another exemplary embodiment, the planar conductive material is a planar conductive material with a low specific surface area, and the BET specific surface area may satisfy 1 m 2 / g and above 40 m 2 / g or less, preferably 5 m 2 / g or more and 30 m 2 / g or less, more preferably 5m 2 / g and above 25 m 2 / g or less.
[0114] As other conductive materials, linear conductive materials such as carbon nanotubes can be cited. The carbon nanotubes can be bundle-type carbon nanotubes. The bundle-type carbon nanotubes can include a plurality of carbon nanotube units. Specifically, unless otherwise specified, the term "bundle-type" used herein refers to a secondary shape in the form of a bundle or rope, in which a plurality of carbon nanotube units are arranged side by side or entangled in substantially the same orientation as the longitudinal axis of the carbon nanotube unit. In the carbon nanotube unit, the graphene sheet is cylindrical with a diameter of nanometers and has a sp 2 In this case, the carbon nanotube unit can exhibit the characteristics of a conductor or a semiconductor depending on the structure and the angle of the rolled graphite sheet. Compared with the tangled carbon nanotubes, the bundled carbon nanotubes can be evenly dispersed during the preparation of the negative electrode, and can improve the conductivity of the negative electrode by smoothly forming a conductive network in the negative electrode.
[0115] Exemplarily, the linear conductive material can be a single-walled carbon nanotube (SWCNT) with a large BET specific surface area, a linear morphology, a very small diameter and a very long length. A linear conductive material such as SWCNT cannot be stretched by dispersion and has a strong ability to return to its original shape when dried. Therefore, a linear conductive material such as SWCNT has a strong strength to return to its original shape when dried, so it is usually present in the form of winding or connecting a negative electrode active material or a secondary aggregate. As a bonding method, the linear conductive material can be adsorbed by van der Waals force.
[0116] In an exemplary embodiment of the present application, a negative electrode composition is provided, wherein a content of the negative electrode conductive material is 10 parts by weight or more and 40 parts by weight or less based on 100 parts by weight of the negative electrode composition.
[0117] In another exemplary embodiment, the negative electrode conductive material may be contained in an amount of 10 parts by weight to 40 parts by weight, preferably 10 parts by weight to 30 parts by weight, and more preferably 10 parts by weight to 25 parts by weight, based on 100 parts by weight of the negative electrode composition.
[0118] In an exemplary embodiment of the present application, a negative electrode composition is provided, wherein the negative electrode conductive material includes a planar conductive material and a linear conductive material.
[0119] In an exemplary embodiment of the present application, a negative electrode composition is provided, wherein the negative electrode conductive material comprises 80 parts by weight or more and 99.9 parts by weight or less of a planar conductive material and 0.1 parts by weight or more and 20 parts by weight or less of a linear conductive material, based on 100 parts by weight of the negative electrode conductive material.
[0120] In another exemplary embodiment, the content of the planar conductive material in the negative electrode conductive material may be 80 parts by weight or more and 99.9 parts by weight or less, preferably 85 parts by weight or more and 99.9 parts by weight or less, and more preferably 95 parts by weight or more and 98 parts by weight or less, based on 100 parts by weight of the negative electrode conductive material.
[0121] In yet another exemplary embodiment, the content of the linear conductive material in the negative electrode conductive material may be 0.1 parts by weight or more and 20 parts by weight or less, preferably 0.1 parts by weight or more and 15 parts by weight or less, and more preferably 2 parts by weight or more and 5 parts by weight or less, based on 100 parts by weight of the negative electrode conductive material.
[0122] In an exemplary embodiment of the present application, because the negative electrode conductive material comprises a planar conductive material and a linear conductive material, and the planar conductive material and the linear conductive material each satisfy the composition and proportion, the negative electrode conductive material has the following characteristics: the service life characteristics of the existing lithium secondary battery will not be greatly affected, especially in the case of comprising a planar conductive material and a linear conductive material, the sites at which the battery can be charged and discharged are increased, so the output characteristics at a high C rate are excellent and the amount of high-temperature gas generated is reduced.
[0123] The negative electrode conductive material according to the present application has a completely different structure from the positive electrode conductive material applied to the positive electrode. That is, the negative electrode conductive material according to the present application is used to capture the contact points between the silicon-based active materials in which the volume expansion of the electrode is very large due to charge and discharge, while the positive electrode conductive material is used to play a buffering role during rolling while imparting partial conductivity, and its structure and role are completely different from those of the negative electrode conductive material of the present invention.
[0124] In addition, the negative electrode conductive material according to the present application is applied to the silicon-based active material and has a completely different structure from the conductive material applied to the graphite-based active material. That is, the conductive material used for the electrode with the graphite-based active material has only small particles relative to the active material, and thus has the characteristics of improving the output characteristics and imparting partial conductivity, and its structure and function are completely different from those of the negative electrode conductive material applied together with the silicon-based active material in the present invention.
[0125] In an exemplary embodiment of the present application, the planar conductive material used as the above-mentioned negative electrode conductive material has a structure and function different from the carbon-based active material generally used as the negative electrode active material. Specifically, the carbon-based active material used as the negative electrode active material may be artificial graphite or natural graphite, and refers to a material that is processed into a spherical or dot shape and used in order to promote the storage and release of lithium ions.
[0126] In contrast, the planar conductive material used as the negative electrode conductive material is a material having a planar or plate-like shape, and can be expressed as plate-like graphite. That is, the planar conductive material is a material contained in order to maintain the conductive path in the negative electrode active material layer, and refers to a material that ensures the conductive path in a planar form in the negative electrode active material layer, rather than playing a role in storing and releasing lithium.
[0127] That is, in the present application, the fact that plate-like graphite is used as a conductive material means that the plate-like graphite is processed into a planar or plate-like shape and used as a material that ensures a conductive path rather than playing a role of storing or releasing lithium. In this case, the negative electrode active material contained together has a high capacity characteristic for storage and release of lithium, and plays a role capable of storing and releasing all lithium ions transmitted from the positive electrode.
[0128] In contrast, in the present application, the fact that a carbon-based active material is used as an active material means that the carbon-based active material is processed into a dot shape or a spherical shape and used as a material for storing or releasing lithium.
[0129] In an exemplary embodiment of the present application, the negative electrode binder may include at least one selected from the group consisting of polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid, ethylene propylene diene monomer rubber (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, polyacrylic acid, and materials in which hydrogen is replaced by Li, Na, Ca, etc., and may also include various copolymers thereof.
[0130] The negative electrode binder according to an exemplary embodiment of the present application plays the role of retaining the active material and the conductive material to prevent the negative electrode structure from being twisted and deformed when the silicon-based active material undergoes volume expansion and relaxation. When the above-mentioned role is met, all common binders can be applied, specifically, water-based binders can be used, and more specifically, PAM-based binders can be used.
[0131] In an exemplary embodiment of the present application, the content of the negative electrode binder may be 30 parts by weight or less, preferably 25 parts by weight or less, more preferably 20 parts by weight or less, and may be 5 parts by weight or more and 10 parts by weight or more, based on 100 parts by weight of the negative electrode composition.
[0132] In an exemplary embodiment of the present application, a negative electrode for a lithium secondary battery is provided, the negative electrode comprising: a negative electrode collector layer; and a negative electrode active material layer formed on one surface or both surfaces of the negative electrode collector layer, the negative electrode active material layer comprising the negative electrode composition according to the present application or a cured product thereof.
[0133] Figure 1 1 is a view showing a stack structure of a negative electrode for a lithium secondary battery according to an exemplary embodiment of the present application. Specifically, it can be confirmed that the negative electrode 100 for a lithium secondary battery includes a negative electrode active material layer 20 on one surface of a negative electrode collector layer 10 .
[0134] According to another exemplary embodiment Figure 2 The stack structure of the negative electrode for a lithium secondary battery is shown, and specifically, it can be confirmed that the negative electrode 100 for a lithium secondary battery includes the negative electrode active material layer 20 on both surfaces of the negative electrode collector layer 10 .
[0135] As mentioned above, there are two types: one is that one surface of the negative electrode current collector layer is coated with a negative electrode active material layer (see Figure 1 ), and the other is that both surfaces of the negative electrode collector layer are coated with a negative electrode active material layer (see Figure 2 ). In this case, the compositions of the negative electrode active material layers coated on both surfaces may be the same or different.
[0136] In an exemplary embodiment of the present application, when both surfaces are coated with a negative electrode active material layer, a negative electrode active material layer comprising a negative electrode composition according to the present application can be used without restriction, as long as only one of the two surfaces is coated with the negative electrode active material layer, and the other surface can contain a silicon-based negative electrode active material or a carbon-based negative electrode active material that can be generally included.
[0137] In an exemplary embodiment of the present application, as for the negative electrode, a negative electrode for a lithium secondary battery may be formed by coating one surface or both surfaces of a current collector with a negative electrode slurry including the negative electrode composition.
[0138] In an exemplary embodiment of the present application, the negative electrode slurry may include: a negative electrode composition; and a slurry solvent.
[0139] In an exemplary embodiment of the present application, the solid content of the negative electrode slurry may satisfy 5% or more and 40% or less.
[0140] In another exemplary embodiment, the solid content of the negative electrode slurry may satisfy a range of 5% to 40% both inclusive, preferably 7% to 35% both inclusive, and more preferably 10% to 30% both inclusive.
[0141] The solid content of the negative electrode slurry may refer to the content of the negative electrode composition contained in the negative electrode slurry, and may refer to the content of the negative electrode composition based on 100 parts by weight of the negative electrode slurry.
[0142] When the solid content of the negative electrode slurry satisfies the above range, the present invention has the following characteristics: since the viscosity is appropriate during the formation of the negative electrode active material layer, the negative electrode active material layer can be efficiently formed by minimizing the aggregation phenomenon of particles of the negative electrode composition.
[0143] In an exemplary embodiment of the present application, the negative electrode collector layer generally has a thickness of 1 μm to 100 μm. There is no particular limitation on the negative electrode collector layer, as long as the negative electrode collector layer has high conductivity without causing chemical changes to the battery, for example, copper, stainless steel, aluminum, nickel, titanium, fired carbon; copper or stainless steel surface-treated with carbon, nickel, titanium, silver, etc.; aluminum-cadmium alloy, etc. In addition, the negative electrode collector layer can also improve the bonding strength of the negative electrode active material by forming fine concave-convex on its surface, and the negative electrode collector layer can be used in various forms such as films, sheets, foils, nets, porous bodies, foams, and non-woven fabrics.
[0144] In an exemplary embodiment of the present application, there is provided a negative electrode for a lithium secondary battery, wherein the negative electrode current collector layer has a thickness of 1 μm or more and 100 μm or less, and the negative electrode active material layer has a thickness of 20 μm or more and 500 μm or less.
[0145] However, the thickness may be variously modified according to the type and purpose of the negative electrode used, and is not limited thereto.
[0146] In an exemplary embodiment of the present application, the porosity of the negative electrode active material layer may satisfy a range of 10% or more and 60% or less.
[0147] In another exemplary embodiment, the porosity of the negative electrode active material layer may satisfy a range of 10% or more and 60% or less, preferably 20% or more and 50% or less, and more preferably 30% or more and 45% or less.
[0148] The porosity varies with the composition and content of the silicon-based active material, conductive material and binder contained in the negative electrode active material layer. In particular, when the silicon-based active material and conductive material according to the present application are contained in a specific composition and content, the above-mentioned range is satisfied, and therefore it is characterized in that the conductivity and resistance in the electrode have an appropriate range.
[0149] In an exemplary embodiment of the present application, a lithium secondary battery is provided, including: a positive electrode; a negative electrode for a lithium secondary battery according to the present application; a separator disposed between the positive electrode and the negative electrode; and an electrolyte.
[0150] Figure 3It is a view showing the stacking structure of a lithium secondary battery according to an exemplary embodiment of the present application. Specifically, a negative electrode 100 for a lithium secondary battery can be confirmed, which includes a negative electrode active material layer 20 on one surface of a negative electrode collector layer 10, and a positive electrode 200 for a lithium secondary battery can be confirmed, which includes a positive electrode active material layer 40 on one surface of a positive electrode collector layer 50, and it is shown that the negative electrode 100 for a lithium secondary battery and the positive electrode 200 for a lithium secondary battery are formed into a structure in which the electrodes are stacked under the condition that a separator 30 is placed therebetween. In addition, the negative electrode active material layer 20 can be formed on both surfaces of the negative electrode collector layer 10. In addition, the positive electrode active material layer 40 can be formed on both surfaces of the positive electrode collector layer 50.
[0151] A secondary battery according to an exemplary embodiment of the present specification may particularly include the above-mentioned negative electrode for a lithium secondary battery. Specifically, the secondary battery may include a negative electrode, a positive electrode, a separator between the positive electrode and the negative electrode, and an electrolyte, and the negative electrode is the same as the above-mentioned negative electrode. Since the negative electrode has been described in detail, its specific description will be omitted.
[0152] The positive electrode may include a positive electrode collector and a positive electrode active material layer formed on the positive electrode collector and including a positive electrode active material.
[0153] In the positive electrode, there is no particular limitation on the positive electrode collector, as long as the positive electrode collector has conductivity and does not cause chemical changes in the battery, for example, stainless steel, aluminum, nickel, titanium, fired carbon; or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. In addition, the positive electrode collector can generally have a thickness of 3 μm to 500 μm, and the adhesion of the positive electrode active material can also be enhanced by forming fine concavoconvexities on the surface of the collector. For example, the positive electrode collector can be used in various forms such as films, sheets, foils, nets, porous bodies, foams, and non-woven fabrics.
[0154] The positive electrode active material may be a commonly used positive electrode active material. Specifically, the positive electrode active material includes: layered compounds such as lithium cobalt oxide (LiCoO2) and lithium nickel oxide (LiNiO2) or compounds substituted by one or more transition metals; lithium iron oxide such as LiFe3O4; lithium manganese oxide such as Li 1+c1 Mn 2-c1 O4 (0≤c1≤0.33), LiMnO3, LiMn2O3 and LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, V2O5 and Cu2V2O7; such as the chemical formula LiNi 1-c2 M c2O2 (wherein M is at least one selected from the following: Co, Mn, Al, Cu, Fe, Mg, B and Ga, and c2 satisfies 0.01≤c2≤0.6) represented by Ni-site lithium nickel oxide; such as the chemical formula LiMn 2-c3 M c3 Lithium manganese composite oxide represented by Li2Mn3MO8 (herein, M is at least one selected from the following: Co, Ni, Fe, Cr, Zn and Ta, and c3 satisfies 0.01≤c3≤0.6); LiMn2O4 in which Li of the chemical formula is partially replaced by alkaline earth metal ions, etc., but not limited thereto. The positive electrode can be Li metal.
[0155] In an exemplary embodiment of the present application, the positive electrode active material contains a lithium composite transition metal compound containing nickel (Ni), cobalt (Co) and manganese (Mn), the lithium composite transition metal compound contains a single particle or a secondary particle, and the single particle may have an average particle size (D 50 ).
[0156] For example, the average particle size (D 50 ) can be greater than 1 μm and less than 12 μm, greater than 1 μm and less than 8 μm, greater than 1 μm and less than 6 μm, greater than 1 μm and less than 12 μm, greater than 1 μm and less than 8 μm, or greater than 1 μm and less than 6 μm.
[0157] Even if a single particle is formed to have an average particle size (D 50 ) small diameter particles, the particle strength can also be excellent. For example, when 650 kgf / cm 2 When the force is extended, a single particle can have a particle strength of 100 to 300 MPa. As a result, even at 650 kgf / cm 2 The phenomenon of increasing the number of particles in the electrode due to particle breakage is also alleviated by strongly rolling single particles, thereby improving the service life characteristics of the battery.
[0158] The single particles can be prepared by mixing a transition metal precursor and a lithium raw material and firing the resulting mixture. The secondary particles can be prepared by a different method from the single particles, and their composition can be the same as or different from that of the single particles.
[0159] The method of forming single particles is not particularly limited, but generally, single particles can be formed by increasing the firing temperature to achieve overfiring, and single particles can be prepared by using additives such as grain growth promoters that assist overfiring or changing raw materials.
[0160] For example, the firing is carried out at a temperature at which a single particle can be formed. In order to form a single particle, the firing needs to be carried out at a higher temperature than in the preparation of the secondary particles, for example, when the composition of the precursor is the same, it is necessary to fire at a temperature of about 30°C to 100°C higher than when preparing the secondary particles. The firing temperature for forming a single particle may vary according to the metal composition in the precursor, for example, when it is desired to form a single particle with a high Ni-NCM lithium composite transition metal oxide having a nickel (Ni) content of more than 80 mol%, the firing temperature may be 700°C to 1000°C, preferably about 800°C to 950°C. When the firing temperature meets the above range, a positive active material comprising a single particle having excellent electrochemical properties can be prepared. When the firing temperature is less than 790°C, a positive active material comprising a lithium composite transition metal compound in the form of a secondary particle can be prepared, and when the firing temperature exceeds 950°C, over-firing may occur, so that the layered crystal structure cannot be formed normally, thereby deteriorating the electrochemical performance.
[0161] In this specification, single particle is a term used in the prior art to distinguish single particles from secondary particles formed by the aggregation of tens to hundreds of primary particles, and is a concept that includes a single particle composed of one primary particle and a quasi-single particle that is an aggregate of 30 or less primary particles.
[0162] Specifically, in the present invention, the single particle may be a single particle composed of one primary particle or in the form of a quasi-single particle which is an aggregate of 30 or less primary particles, and the secondary particle may be an aggregate composed of several hundred primary particles.
[0163] In an exemplary embodiment of the present application, the lithium composite transition metal compound as the positive electrode active material further includes secondary particles, and the average particle size (D 50 ) is smaller than the average particle size of the secondary particles (D 50 ).
[0164] In the present invention, the single particle may be in the form of a single particle composed of one primary particle or a quasi-single particle which is an aggregate of 30 or less primary particles, and the secondary particle may be in the form of an aggregate of several hundred primary particles.
[0165] The lithium composite transition metal compound may further include secondary particles. Secondary particles refer to a form formed by aggregation of primary particles and can be distinguished from the concept of single particles, which include one primary particle, one single particle, or a quasi-single particle that is an aggregate of 30 or less primary particles.
[0166] The secondary particles may have a particle size (D50 ). The secondary particles may have a size of 0.05 m 2 / g to 10 m 2 / g, preferably 0.1 m 2 / g to 1 m 2 / g, more preferably 0.3 m 2 / g to 0.8 m 2 / g specific surface area (BET).
[0167] In other exemplary embodiments of the present application, the secondary particles are aggregates of primary particles, and the primary particles have an average particle size (D 50 Specifically, the secondary particles may be in the form of aggregation of several hundred primary particles, and the primary particles may have an average particle size (D 50 ).
[0168] When the average particle size of the primary particles (D 50 When the average particle size of the primary particles (D 50 ) is too small, the number of primary particles that form the aggregation of lithium nickel oxide particles increases, thereby reducing the effect of suppressing the breakage of particles during rolling. 50 ) is too large, the lithium diffusion path inside the primary particle becomes long, so that the resistance increases and the output characteristics may deteriorate.
[0169] According to other exemplary embodiments of the present application, the average particle size (D 50 ) is characterized by being smaller than the average particle size of the secondary particles (D 50 ). Therefore, even if a single particle is formed of a small-diameter particle, the single particle can have excellent particle strength, and the excellent particle strength can alleviate the phenomenon that the number of fine particles in the electrode increases due to particle breakage, thereby improving the service life characteristics of the battery.
[0170] In an exemplary embodiment of the present application, the average particle size (D 50 ) is smaller than the average particle size of the secondary particles (D 50 ) as small as 1 μm to 18 μm.
[0171] For example, the average particle size (D 50 ) can be compared with the average particle size of the secondary particles (D 50 ) is 1 μm to 16 μm, 1.5 μm to 15 μm, or 2 μm to 14 μm.
[0172] When the average particle size of a single particle (D 50 ) is smaller than the average particle size of the secondary particles (D 50 ), for example, when the above-mentioned range is met, even if a single particle is formed with a small particle size, a single particle can have excellent particle strength. Therefore, the excellent particle strength alleviates the phenomenon of an increase in the number of particles in the electrode due to particle breakage, thereby having the effect of improving the service life characteristics of the battery and increasing the battery energy density.
[0173] According to other exemplary embodiments of the present application, the content of the single particle may be 15 to 100 parts by weight based on 100 parts by weight of the positive electrode active material. The content of the single particle may be 20 to 100 parts by weight, or 30 to 100 parts by weight based on 100 parts by weight of the positive electrode active material.
[0174] For example, based on 100 parts by weight of the positive electrode active material, the content of the single particle may be 15 parts by weight or more, 20 parts by weight or more, 25 parts by weight or more, 30 parts by weight or more, 35 parts by weight or more, 40 parts by weight or more, or 45 parts by weight or more. Based on 100 parts by weight of the positive electrode active material, the content of the single particle may be 100 parts by weight or less.
[0175] When the single particle is included within the above range, excellent battery characteristics can be exhibited in combination with the above negative electrode material. Specifically, when the amount of the single particle is 15 parts by weight or more, the phenomenon of an increase in the number of particles in the electrode due to particle rupture during the rolling process after manufacturing the electrode can be alleviated, thereby improving the service life characteristics of the battery.
[0176] In an exemplary embodiment of the present application, the lithium composite transition metal compound may further include secondary particles, and the amount of the secondary particles may be 85 parts by weight or less based on 100 parts by weight of the positive electrode active material. Based on 100 parts by weight of the positive electrode active material, the amount of the secondary particles may be 80 parts by weight or less, 75 parts by weight or less, or 70 parts by weight or less. Based on 100 parts by weight of the positive electrode active material, the amount of the secondary particles may be 0 parts by weight or more.
[0177] When the above range is met, the above effect caused by the presence of a single particle of positive electrode active material can be maximized. When a secondary particle of positive electrode active material is included, the component may be the same as the component exemplified as the above single particle positive electrode active material, may be a different component, and may refer to an aggregated form of a single particle form.
[0178] In an exemplary embodiment of the present application, in 100 parts by weight of the positive electrode active material layer, the content of the positive electrode active material can be 80 parts by weight or more and 99.9 parts by weight or less, preferably 90 parts by weight or more and 99.9 parts by weight or less, more preferably 95 parts by weight or more and 99.9 parts by weight or less, and even more preferably 98 parts by weight or more and 99.9 parts by weight or less.
[0179] The positive electrode active material layer may include a positive electrode conductive material and a positive electrode binder as well as the positive electrode active material.
[0180] In this case, the positive electrode conductive material is used to provide conductivity to the electrode, and can be used without particular limitation as long as the positive electrode conductive material has electronic conductivity without causing chemical changes in the battery to be constructed. Specific examples thereof include: graphite such as natural graphite or artificial graphite; carbon-based materials such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; metal powder or metal fiber such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, and any one of them or a mixture of two or more thereof may be used.
[0181] In addition, the positive electrode binder is used to improve the bonding between the positive electrode active material particles and the adhesion between the positive electrode active material and the positive electrode collector. Its specific examples may include polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene monomer rubber (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber or its various copolymers, and any one thereof or a mixture of two or more thereof may be used.
[0182] The separator separates the negative electrode from the positive electrode and provides a path for the movement of lithium ions, and can be used without particular restrictions, as long as the separator is generally used as a separator in a secondary battery, and in particular, a separator having excellent moisture retention ability for electrolytes and low resistance to electrolyte ion migration is preferred. Specifically, porous polymer films, such as porous polymer films formed by polyolefin-based polymers such as ethylene homopolymers, propylene homopolymers, ethylene / butene copolymers, ethylene / hexene copolymers, and ethylene / methacrylate copolymers, can be used; or a laminated structure of two or more layers thereof. In addition, typical porous non-woven fabrics, such as non-woven fabrics made of high melting point glass fibers or polyethylene terephthalate fibers, etc., can also be used. In addition, a coated separator comprising a ceramic component or a polymer material can be used to ensure heat resistance or mechanical strength, and a single-layer or multi-layer structure can be selectively used.
[0183] Examples of the electrolyte include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel-type polymer electrolytes, solid inorganic electrolytes, molten inorganic electrolytes, etc., which can be used to prepare lithium secondary batteries, but are not limited thereto.
[0184] Specifically, the electrolyte may include a nonaqueous organic solvent and a metal salt.
[0185] As the nonaqueous organic solvent, for example, an aprotic organic solvent such as N-methyl-2-pyrrolidone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, triester phosphate, trimethoxymethane, dioxolane derivatives, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate and ethyl propionate can be used.
[0186] In particular, among carbonate-based organic solvents, cyclic carbonates such as ethylene carbonate and propylene carbonate can be preferably used. This is because cyclic carbonates as high-viscosity organic solvents have a high dielectric constant, thereby dissociating lithium salts well, and when cyclic carbonates are mixed with low-viscosity and low-dielectric-constant linear carbonates such as dimethyl carbonate and diethyl carbonate in an appropriate ratio, an electrolyte with high conductivity can be prepared, so such a combined use is more preferred.
[0187] As the metal salt, a lithium salt which is a material easily soluble in a non-aqueous electrolyte may be used, and as an anion of the lithium salt, for example, one or more selected from the following may be used: F - , Cl - ,I - 、NO3 - 、N(CN)2 - 、BF4 - 、ClO4 - PF6 - 、(CF3)2PF4 - 、(CF3)3PF3 - 、(CF3)4PF2 - 、(CF3)5PF - 、(CF3)6P - CF3SO3 - CF3CF2SO3 - 、(CF3SO2)2N - 、(FSO2)2N- CF3CF2(CF3)2CO - 、(CF3SO2)2CH - 、(SF5)3C - 、(CF3SO2)3C - CF3(CF2)7SO3 - CF3CO2 - 、CH3CO2 - 、SCN - and (CF3CF2SO2)2N - .
[0188] In the electrolyte, in order to improve the service life characteristics of the battery, inhibit the reduction of the battery capacity, and increase the discharge capacity of the battery, on the basis of containing the above-mentioned electrolyte components, for example, one or more additives such as the following may be included: halogenated alkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, (condensed) glycol dimethyl ethers, hexamethylphosphoric triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted Oxazolidinone, N,N-substituted imidazolidine, ethylene glycol dialkyl ether, ammonium salt, pyrrole, 2-methoxyethanol or aluminum trichloride.
[0189] The exemplary embodiment of the present invention provides a battery module including the secondary battery as a unit cell and a battery pack including the battery module. Since the battery module and the battery pack include the secondary battery with high capacity, high rate performance and high cycle characteristics, they can be used as a power source for medium and large devices selected from the following: electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles and power storage systems.
[0190] Preferred Embodiments
[0191] Hereinafter, preferred embodiments will be proposed to help understand the present invention, but these embodiments are provided only to illustrate the present invention, and it is obvious to those skilled in the art that various substitutions and variations within the scope of the present invention and the technical spirit are possible. Naturally, such substitutions and variations also fall within the scope of the appended claims.
[0192] <Preparation Example>
[0193] <Preparation of Negative Electrode Composition>
[0194] By using Si (average particle size (D 50): 5 μm), a metal composite, a first conductive material, a second conductive material and polyacrylamide (PAM) as a binder satisfying the composition and content in Table 1 below were added to distilled water as a solvent for forming a negative electrode slurry in a weight ratio as shown in Table 1 below to prepare a negative electrode slurry (solid concentration of 28 wt %).
[0195] In this case, the first conductive material, the second conductive material, and the binder were used in amounts of 9.685 parts by weight, 0.315 parts by weight, and 10 parts by weight, respectively, based on 100 parts by weight of the negative electrode slurry.
[0196] Specifically, the first conductive material is plate-like graphite (specific surface area: 17 m 2 / g, average particle size (D 50 ): 3.5 μm), and the second conductive material is SWCNT.
[0197] As a specific mixing method, after the first conductive material, the second conductive material, the binder and water were dispersed at 2500 rpm for 30 minutes using a homomixer, the silicon-based active material was added thereto, and then the resulting mixture was dispersed at 2500 rpm for 30 minutes to prepare a negative electrode slurry.
[0198] 85 mg / 25 cm 2 Both surfaces of a copper current collector (thickness: 8 μm) as a negative electrode current collector layer were coated with the negative electrode slurry, and the copper current collector was rolled and dried in a vacuum oven at 130°C for 10 hours to form a negative electrode active material layer (thickness: 33 μm), which was used as a negative electrode (negative electrode thickness: 41 μm, negative electrode porosity: 40.0%).
[0199]
[0200] <Manufacturing of Secondary Battery>
[0201] By using LiNi as the positive electrode active material 0.6 Co 0.2 Mn 0.2 O2 (average particle size (D 50 ): 15 μm), carbon black (product name: Super C65, manufacturer: Timcal) as a conductive material and polyvinylidene fluoride (PVdF) as a binder were added to N-methyl-2-pyrrolidone (NMP) as a solvent for forming a positive electrode slurry in a weight ratio of 97:1.5:1.5 to prepare a positive electrode slurry (solid concentration of 78 wt %).
[0202] The positive electrode slurry was prepared at 537 mg / 25 cm 2The positive electrode was prepared by coating the positive electrode active material layer (thickness: 65 μm) with a loading amount of 240 μm on both surfaces of an aluminum collector (thickness: 12 μm) as a positive electrode collector, and the aluminum collector was rolled and dried in a vacuum oven at 130°C for 10 hours to form a positive electrode active material layer (thickness: 65 μm), thereby preparing a positive electrode (positive electrode thickness: 77 μm, porosity: 26%).
[0203] A lithium secondary battery was prepared by inserting a polyethylene separator between the positive electrode and the negative electrode of each of Examples and Comparative Examples and injecting an electrolyte therein.
[0204] The electrolyte was obtained by adding 3 wt % of vinylene carbonate based on the total weight of the electrolyte to an organic solvent in which fluoroethylene carbonate (FEC) and diethyl carbonate (DEC) were mixed in a volume ratio of 10:90, and then adding LiPF6 as a lithium salt thereto at a concentration of 1 M.
[0205] Experimental Example 1: Evaluation of Single Battery Life
[0206] The service life of the secondary battery containing the negative electrode prepared in the embodiment and the comparative example was evaluated using an electrochemical charge and discharge device, and the capacity retention rate was evaluated. The secondary battery was subjected to an in-situ cycle test at 4.2 to 3.0 V and 1C / 0.5C, and the capacity retention rate was measured by charging / discharging the secondary battery at 0.33C / 0.33C (4.2 to 3.0 V) every 50 cycles during the test, and the results are shown in Table 2.
[0207] Capacity retention rate (%) = {(discharge capacity at the Nth cycle) / (discharge capacity at the first cycle)} × 100
[0208]
[0209] Experimental Example 2: Evaluation of 0.1 s discharge resistance of initial cycle at SOC 50 2.5C (electrode resistance measurement using a single cell)
[0210] During the test of Experimental Example 1, the secondary battery was charged / discharged at 0.33C / 0.33C (4.2-3.0 V) every 50 cycles, and the capacity retention rate was measured. Then, during the discharge at 2.5C pulse at SOC 50, the resistance value within a certain period of time (0.1 s to 10 s) was measured, and the results are shown in Table 3 below.
[0211]
[0212] As can be seen from Tables 1 to 3 above, it can be confirmed that when the metal composite according to the present application is used, the SOC of silicon itself is limited compared to when the silicon-based active material is used alone (compared to Comparative Example 1), so the effect of improving the service life performance is shown. That is, the metal composite has the above-mentioned characteristics, thereby reacting with lithium at a higher potential than the silicon-based active material and having excellent reactivity, thereby suppressing the volume expansion of the silicon-based active material during the charge and discharge process compared to when the silicon-based active material is used alone, and it can be confirmed that the metal composite has the characteristics of excellent effect of improving the service life performance.
[0213] Comparative Example 1 corresponds to the case where the metal composite according to the present application is not included, and Comparative Example 2 corresponds to the case where the metal composite according to the present application is not used but the metal (Sn) is used alone. In addition, Comparative Example 3 corresponds to the case where the proportion of the metal in the metal composite is small, and Comparative Example 4 corresponds to the case where the proportion of the metal in the metal composite is high.
[0214] When comparing Comparative Example 1 with the embodiment, it can be confirmed that there is an effect of improving the service life performance, and it can be confirmed that the electrode of the embodiment maintains a low resistance. This corresponds to the result that the effect of improving the service life performance is shown due to the limitation of the SOC of silicon itself.
[0215] In addition, Comparative Example 2 is a case where a metal is used in the negative electrode, and it can be confirmed that a relative imbalance occurs between the upper and lower parts of the electrode, and therefore, since lithium ions need to enter from the upper part of the electrode to the lower part during the first discharge, the service life performance is deteriorated. However, in the case of the embodiment, the lithium oxide can be uniformly mixed, so that it can be confirmed that when the initial electrochemical reaction occurs, the lithium ions are distributed as a whole at the upper and lower ends of the electrode, so that the lithium ions can be introduced more uniformly, and thus the effect of improving the curvature can be shown.
[0216] In the case of Comparative Examples 3 and 4, the weight ratio of the metal in the metal oxide to the lithium oxide was adjusted, and it was confirmed that when the weight ratio exceeded or was lower than the range according to the present application, the expected effect could not be achieved.
Claims
1. A negative electrode composition, comprising: Silicon-based active materials; A negative electrode conductive material; and Negative electrode binder, wherein the negative electrode composition comprises a metal composite having lithium oxide deposited thereon, The weight ratio of the metal to the lithium oxide in the metal composite satisfies 10:1 or more and 800:1 or less, and The content of the metal composite is 1 part by weight or more and 15 parts by weight or less based on 100 parts by weight of the negative electrode composition. 2 . The negative electrode composition according to claim 1 , wherein the content of the silicon-based active material is 60 parts by weight or more based on 100 parts by weight of the negative electrode composition.
3. The negative electrode composition according to claim 1, wherein the silicon-based active material comprises one or more selected from SiO where x = 0 x , SiO where 0 < x < 2 x , SiC, and Si alloys.
4. The negative electrode composition according to claim 1, wherein the silicon-based active material comprises one or more selected from SiO where x = 0 x and SiO where 0 < x < 2 x , and based on 100 parts by weight of the silicon-based active material, the content of SiO where x = 0 x is 70 parts by weight or more. 5 . The negative electrode composition according to claim 1 , wherein the lithium oxide has a D50 particle size of 200 nm or less.
6. The negative electrode composition according to claim 1, wherein a weight ratio of the metal composite to the silicon-based active material in the negative electrode composition satisfies 1:5 to 1:
20. 7 . The negative electrode composition according to claim 1 , wherein a content of the negative electrode conductive material is 10 parts by weight or more and 40 parts by weight or less based on 100 parts by weight of the negative electrode composition. 8 . The negative electrode composition according to claim 1 , wherein the negative electrode conductive material comprises a planar conductive material and a linear conductive material. 9 . The negative electrode composition according to claim 8 , wherein the negative electrode conductive material comprises 80 parts by weight or more and 99.9 parts by weight or less of the planar conductive material and 0.1 parts by weight or more and 20 parts by weight or less of the linear conductive material, based on 100 parts by weight of the negative electrode conductive material. 10 . The negative electrode composition according to claim 1 , wherein a content of the negative electrode binder is 5 parts by weight or more and 30 parts by weight or less based on 100 parts by weight of the negative electrode composition.
11. A negative electrode for a lithium secondary battery, the negative electrode comprising: a negative electrode current collector layer; and a negative electrode active material layer, the negative electrode active material layer being disposed on one surface or both surfaces of the negative electrode current collector layer, The negative electrode active material layer comprises the negative electrode composition according to any one of claims 1 to 10 or a cured product thereof.
12. The negative electrode according to claim 11, wherein the negative electrode current collector layer has a thickness of 1 μm or more and 100 μm or less, and The negative electrode active material layer has a thickness of 5 μm or more and 500 μm or less.
13. A lithium secondary battery, comprising: positive electrode; The negative electrode for a lithium secondary battery according to claim 11; A separator disposed between the positive electrode and the negative electrode; and Electrolytes.
Citation Information
Patent Citations
Anode for lithium ion battery
JP2009080971A